Carbon-ion radiotherapy for inoperable endometrial carcinoma. (8th March 2018) - Irie, Daisuke; Okonogi, Noriyuki; Wakatsuki, Masaru; Kato, Shingo; Ohno, Tatsuya; Karasawa, Kumiko; Kiyohara, Hiroki; Kobayashi, Daijiro; Tsuji, Hiroshi; Nakano, Takashi; Kamada, Tadashi; Shozu, Makio; et al.
Abstract: This is a pooled analysis to evaluate the toxicity and efficacy of carbon-ion radiotherapy (C-ion RT) for inoperable endometrial carcinoma. Eligible patients had previously untreated Stage I–III endometrial carcinoma without para-aortic lymph node metastasis. Total dose to the tumor was 62.4–74.4 Gy [relative biological effectiveness (RBE)] in 20 fractions, and the dose to the gastrointestinal tract was limited to <60 Gy (RBE). Intracavitary brachytherapy was not combined in the present study. Fourteen patients with endometrial carcinoma were analyzed. Ten of the 14 patients were judged medically inoperable, and the others refused surgery. The numbers of patients with Stage I, II and III disease were 1, 9 and 4, respectively. Tumor size was 3.8–13.8 cm in maximum diameter. Median follow-up periods for all patients and surviving patients were 50 months (range, 12–218 months) and 78 months (range, 23–218 months), respectively. Two of three patients receiving 62.4–64.8 Gy (RBE) had local recurrence whereas none of 11 patients receiving 68.0 Gy (RBE) or more had local recurrence. Three patients developed distant metastases and one of them also had local recurrence. The 5-year local control, progression-free survival, overall survival, and cause-specific survival rates were 86%, 64%, 68% and 73%, respectively. No patient developed Grade 3 or higher acute or late toxicity. The present study showed that C-ion RT alone could be a safe and curative treatment modality for inoperable endometrial carcinoma.